Evaluation of Potentially Inappropriate Medication Use in Elderly Patients Using Beers Criteria in Community Pharmacy - Guru., G; kakadiya, Jagadish; Lavanya, S. (International Journal of Pharmaceutical Investigation, 2026)
Background With a mature worldwide population, the safety and appropriateness of the medications prescribed to older adults become ever more important. This study expected to determine the occurrence and categorization of 'Potentially Inappropriate Medications' (PIMs) in aged patients, using Beers and STOPP (Screening Tool of Older People's Prescriptions) criteria. Materials and Methods 500 patients (age≥65 years) were included. Demographics, comorbidities, medications prescribed, and PIMs were collected. Descriptive statistics and a series of bi-variate analyses investigated differences between patients with and without PIMs. Results The results showed that 41.27% of patients were prescribed at least one PIM according to Beers criteria and 37.44% according to STOPP criteria. Pantoprazole, gliclazide, and furosemide were common PIMs identified. Inappropriate prescribing of cardiovascular and gastrointestinal medications was common. This found significant associations between PIMs and factors including age, polypharmacy, and comorbidities. Conclusion Older adults should receive regular medication reviews to prevent adverse drug events and to improve clinical outcomes. To reduce the use of PIM in this vulnerable population, targeted interventions e.g., updating prescribing practices and educating health care professionals, will be required.
Keywords: Potentially Inappropriate Medications; Beers Criteria; STOPP Criteria; Elderly Patients; Adverse Drug Events.